An evaluation of commercial radioisotope methods for the determination of folate and vitamin B12. Issue 3 (March 1980) - Dawson, D W; Delamore, I W; Fish, D I; Flaherty, T A; Gowenlock, A H; Hunt, L P; Hyde, K; MacIver, J E; Thornton, J A; Waters, H M
Abstract : Five commercial kits for the determination of folate and six kits for the determination of vitamin B12 were investigated. Their performance has been compared with microbiological methods for the two vitamins and with a non-commercial radioisotopic method for B12. The results show the importance of the determination of the reference range for an individual laboratory for each method. The precision of the kits varied appreciably, as did their performance using specimens from patients with different haematological disorders. In particular, certain kits failed to detect all patients with pernicious anaemia. The relative accuracy of the kits was assessed. Various factors which should be taken into account in the final selection of a satisfactory kit are discussed.